2022
DOI: 10.3389/fneur.2022.963968
|View full text |Cite
|
Sign up to set email alerts
|

aEYE: A deep learning system for video nystagmus detection

Abstract: BackgroundNystagmus identification and interpretation is challenging for non-experts who lack specific training in neuro-ophthalmology or neuro-otology. This challenge is magnified when the task is performed via telemedicine. Deep learning models have not been heavily studied in video-based eye movement detection.MethodsWe developed, trained, and validated a deep-learning system (aEYE) to classify video recordings as normal or bearing at least two consecutive beats of nystagmus. The videos were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Early proof of concept results are very promising. 45,46 ‘Deep learning’ models would allow nystagmus identification and interpretation, 47 but have some way to go before being commercially available.…”
Section: Role Of Technologymentioning
confidence: 99%
“…Early proof of concept results are very promising. 45,46 ‘Deep learning’ models would allow nystagmus identification and interpretation, 47 but have some way to go before being commercially available.…”
Section: Role Of Technologymentioning
confidence: 99%
“…After the removal of duplicates, the titles and abstracts of 289 publications were screened. Based on the inclusion and exclusion criteria, the full texts of 38 publications were read, 18 publications were excluded, and 20 publications were included in this review (Figure 1, Multimedia Appendix 1 [3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]). Among the 20 studies that reported the use of a device or app, 2 were related to anamnesis and subjective symptoms [3,8], 12 were related to objective examination [8][9][10][11][12][13][14][15][16][17][18][19], 7 were related to remote diagnosis [9,11,15,16,18,20], and 7 were related to treatment and rehabilitation [20][21][22][23][24]…”
Section: Overviewmentioning
confidence: 99%
“…However, we have reached the conclusion that any model that seeks to address these problems must be lightweight and patient-centric design to facilitate efficient diagnostic workflow. Recent studies have utilized webcams ( 8 ) and smartphones ( 9 ) as well as video-oculographic devices ( 10 ) for detection of nystagmus. Thus, we have developed a new technology capable of continuously tracking eye movements by recognizing regions of the ocular.…”
Section: Introductionmentioning
confidence: 99%